Grammatical errors analysis in the descriptive writing of the semester 3 students of English Education Department of STAIN Gajah Putih - Wahyuningsih, Sungkawati Kardi (LPPM UNY, 2015)
This study was aimed at describing: (1) the types of grammatical errors in the descriptive writing of the semester 3 students of English education department of STAIN Gajah Putih, and (2) the causes of the grammatical errors in the descriptive writing of the semester 3 students of English education department of STAIN Gajah Putih. The participants were 60 students of the Semester 3 of English education department of STAIN Gajah Putih in the academic year 2013/2014 chosen randomly. The study consisted of ï¬ ve steps, namely: data collection, error identiï¬ cation, error quantiï¬ cation, error description, and error explanation. The research instrument was in the form of a writing assignment. The data were obtained from the students' writing products. The results of the study are as follows. The total errors found in the students' writing test are 688 that divided into fourteen types of errors, namely: errors in production of verb (57%), miscellaneous errors (21%), errors in the use of preposition (15%), errors in the use of articles (4%), and errors in the distribution of verb group (3%). Then, the causes of errors are as follows: interference (32%), ignorance of rule restriction (21%), incomplete application of rules (19%), false concepts hypothesized (16%), and overgeneralization (12%).